2008
DOI: 10.1890/07-1135.1
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity and Survival in Relation to Resistance to Oxidative Stress in a Free‐living Bird

Abstract: Major life history traits, such as fecundity and survival, have been consistently demonstrated to covary positively in nature, some individuals having more resources than others to allocate to all aspects of their life history. Yet, little is known about which resources (or state variables) may account for such covariation. Reactive oxygen species (ROS) are natural by-products of metabolism and, when ROS production exceeds antioxidant defenses, organisms are exposed to oxidative stress that can have deleteriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
194
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 199 publications
(211 citation statements)
references
References 50 publications
(91 reference statements)
15
194
1
1
Order By: Relevance
“…The deleterious effect of oxidative stress along aging, for example, can negatively affect both cognitive performance and reproductive success (Finkel and Holbrook, 2000;Fukui et al, 2002;Bize et al, 2008;Monaghan et al, 2009), leading to a positive correlation between these two variables. A direct experimental manipulation of problem-solving performance would be needed to confirm the causal link to reproductive success, but this may involve procedures such as manipulating conditions during development to affect the ontogeny of cognitive abilities in future recruits, which may prove difficult to implement in the field.…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious effect of oxidative stress along aging, for example, can negatively affect both cognitive performance and reproductive success (Finkel and Holbrook, 2000;Fukui et al, 2002;Bize et al, 2008;Monaghan et al, 2009), leading to a positive correlation between these two variables. A direct experimental manipulation of problem-solving performance would be needed to confirm the causal link to reproductive success, but this may involve procedures such as manipulating conditions during development to affect the ontogeny of cognitive abilities in future recruits, which may prove difficult to implement in the field.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that individuals that survive over winter and/or migrate later are already physiologically different from other fish in the autumn. Bize et al (2008) showed that in the alpine swift (Apus melba), males with higher resistance to oxidative stress tended to survive to the next season. Taken together, these findings suggest that lower oxidative stress levels may promote survival in wild organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Alonso-Alvarez et al [8] showed experimentally that reproduction is associated with an increased susceptibility to oxidative stress and proposed the hypothesis that this mechanism could explain breeding immunosuppression. Oxidative stress has thus recently gained considerable interest as a mediator of life-history trade-offs [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…As emphasized by Costantini [11], ecological studies on the costs of reproduction have mainly focused on the stress response mediated by glucocorticoids, whereas the links between oxidative stress and life-history traits have been largely ignored [10,11,30] (but see [13,31]). In the present study performed in natural conditions, we experimentally investigated the effect of parental investment on both the capacity of blood cell resistance against a free-radical attack and on blood parasite susceptibilities.…”
Section: Introductionmentioning
confidence: 99%